Minsa'y isang gamu-gamo - Concio, Lupita Aquino; Gonzales, Marina Feleo-; Aunor, Nora; Ilagan, Jay; Bautista, Perla; Sevilla, Gloria; Villayamayor, Eddia; Salcedo, Paquito (Viva Video, 1976)
Tells a story of a lady nurse whose ambition is to migrate to the US. Because of her ambition, she ignores the injustices brought about by the American military presence in the country. On the eve of her travel, an American soldier accidentally shoots and kills her younger brother.